Genotype x Environment Interaction for Yield and Yield Components in Some Sunflower (Helianthus annuus L.) Hybrids * (University of Khartoum Journal of Agricultural Sciences, 2025)
A field experiment was carried out at two locations, New Halfaand Rahad, in the summer of 2003/04 and winter of 2004/05 to estimatethe genotype x environment interaction for yield and its componentsamong 19 locally developed sunflower (Helianthus annuus L.) hybridsand one introduced hybrid (Hysun 33). A randomized complete blockdesign with four replications was used at each location. Data on yield andits components; namely, number of seeds/head, percentage of emptyseeds, 1000-seed weight and seed yield/plant, were collected. Thecombined analysis of variance for all characters showed highly significantdifferences at the genotype level. The genotype x season interaction wasonly significant for 1000-seed weight and seed yield/ha. The genotype xlocation interaction was significant for 1000-seed weight, seed yield/plantand seed yield/ha, whereas genotype x season x location interaction wasonly significant for 1000-seed weight. The number of seeds/head and thepercentage of empty seeds showed non-significant differences at the firstand second order interactions. The highest yield per hectare and per plantaveraged over the four environments was recorded for Hysun 33, whereasthe lowest ones were scored by Ka99x11. The analysis of genotype xenvironment interaction for 1000-seed weight, seed yield/plant and seedyield/ha showed that the major part of the variance was due to non-linearcomponents. The significant differences among the evaluated hybrids atthe different interaction levels suggest that seed yield of sunflower ishighly dependent upon the environmental conditions. Therefore, multi-location testing for several years is needed to identify high yielding stablehybrids.